Strength and sources of self-efficacy beliefs by physical education student teachers - Iaochite, Roberto Tadeu; Souza, Samuel De (Universidade Estadual Paulista, 2014)
In the teaching domain, self-efficacy (SE) is related to teachers' judgment about their own ability to achieve learning outcomes and student engagement. SE is formed by four sources of information: mastery experiences, vicarious experiences, social persuasion, and psychophysiological states. We measured and analyzed SE and its sources for teaching physical education. Student teachers (n = 114) from three universities responded to two Likert scales - Physical Education Teacher Self-Efficacy Scale and Teacher Self-Efficacy Scale Sources - and a social demographic questionnaire. SE for teaching was classified as moderate, and vicarious experiences and social persuasion were the main sources of information. Results were discussed for future researches related to teaching practices in undergraduate programs as well as in-service teacher training.

En el campo de la enseñanza, la auto-eficacia (AE) se relaciona con el juicio de los docentes sobre su propia capacidad de lograr los resultados del aprendizaje y la participación de los estudiantes. AE está formada por cuatro fuentes: las experiencias de maestría, las experiencias vicarias, persuasión social y estados psico-fisiológicos. Se midió y analizó la AE y sus fuentes para la enseñanza de la educación física. Los aprendices (n = 114) de tres universidades respondieron a dos escalas tipo Likert - Escala de Auto-eficacia del Profesor de Educación Física y Escala de Fuentes de Auto-eficacia, y un cuestionario socio demográfico. AE para la enseñanza fue clasificado como moderado, y las experiencias vicarias y persuasión social fueron las principales fuentes de información. Se discuten los resultados para futuras investigaciones relacionadas con las prácticas de enseñanza en los cursos de pregrado, así como programas de capacitación para maestros en servicio.

No domínio do ensino, a autoeficácia (AE) está relacionada com o julgamento dos professores sobre a sua própria capacidade para atingir resultados de aprendizagem e engajamento dos alunos. AE é formada por quatro fontes de informação: experiências diretas, experiências vicárias, persuasão social e estados psicofisiológicos. Nós medimos e analisamos a AE e suas origens para o ensino de educação física. Estagiários (n = 114) de três universidades responderam a duas escalas de Likert - Escala de Autoeficácia do Professor de Educação Física e Escala de Fontes de Autoeficácia, e a um questionário sociodemográfico. AE para o ensino foi classificada em grau moderado; experiências vicárias e persuasão social foram as principais fontes de informação. Os resultados foram discutidos para futuras investigações relacionadas com as práticas de ensino em cursos de graduação, bem como em programas de formação de professores em serviço.
Fuerza y el origen de las creencias en aprendices auto-eficacia en la educación física
Força e origem de crenças na autoeficácia de estagiários em educação física
Keywords: self-efficacy; teacher training; physical education; autoeficácia; formação de professor; educação física